Policy and practice - Scruggs, Thomas E., 1948-; Mastropieri, Margo A., 1951- (Bingley, UK : Emerald-JAI, 2009)
In the study of learning and behavioral disabilities, effective practice and public policy enacted to implement this practice are closely intertwined. In this volume, a number of internationally prominent authors discuss issues and advances both in public policy, and in state-of-the art practice in providing service for individuals with learning and behavioral disabilities. Topics include educational equity, imputations of malice in social policy, analytical discussions of Response to Intervention and No Child Left Behind legislation, policy implications of functional behavioral assessment, implications of poverty for educational policy, and public policy implications of the Higher Education Opportunity Act. In addition, chapters are included that address recent advances in practice for individuals with learning and behavioral disabilities. These topics include interventions for students with Attention Deficit Hyperactivity Disorder, mathematics interventions for individuals with nonverbal learning disabilities, Response-to-Intervention and other literacy practices for students with learning and behavioral disabilities, and the design of functional assessment for challenging behavior. The chapters included in this volume provide important current information on policy and practice for individuals with learning and behavioral disabilities, and will be of interest to teachers, administrators, graduate students, researchers, professionals in personnel preparation programs, and individuals interested in public policy.
Special education in the new millennium: achieving educational equity for students with learning and behavioral disabilities / Margaret J. McLaughlin, Michael P. Krezmien, Mark Zablocki -- Attributions of malice to special education policy and practice / James M. Kauffman -- Response to intervention: a reality check / Amanda Kloo, Naomi Zigmond -- The No Child Left Behind Act and high school graduation for students with and without disabilities / Wendy Morrison Cavendish -- Functional behavioral assessment and students with emotional/behavioral disorders: when research, policy, and practice collide / Maureen A. Conroy, Peter J. Alter, Terrance M. Scott -- The impact of poverty on special education students / Elizabeth Halloran Tornquist, Margo A. Mastropieri, Thomas E. Scruggs, Hugh G. Berry, William D. Halloran -- Increasing access to higher education for students with disabilities and strengthening the preparation of professionals who instruct them: The Higher Education Opportunity Act of 2008 / Jane E. West -- Intervention with students with ADHD: Analysis of the effects of a multi-component and multi-contextualized program on academic and socio-emotional adjustment / Ana Miranda, María Jesús Presentación, Rosa García, Rebeca Siegenthaler -- Nonverbal learning disabilities and arithmetic problems: the effectiveness of an explicit verbal instruction model / Johannes E.H. Van Luit -- Implementing response to intervention: the synergy of beginning reading instruction and early intervening services / Stephanie Al Otaiba, Carol MacDonald Connor, Barbara Foorman, Luana Greulich, Jessica S. Folsom -- Advances in literacy practices for students with emotional and behavioral disabilities / Kelley S. Regan, Thomas E. Scruggs, Margo A. Mastropieri -- Designing functional assessment-based interventions using a systematic approach: a promising practice for supporting challenging behavior / Kathleen Lynne Lane, Allison L. Bruhn, Mary E. Crnobori, Anne Louise Sewell.
Includes bibliographical references.
Description based on print version record.
Keywords: Special education; Learning disabled children -- Education; Teaching of specific groups & persons with special educational needs; Education -- Special Education -- Learning Disabilities